2020
DOI: 10.3390/cancers12030580
|View full text |Cite
|
Sign up to set email alerts
|

Serine Biosynthesis Pathway Supports MYC–miR-494–EZH2 Feed-Forward Circuit Necessary to Maintain Metabolic and Epigenetic Reprogramming of Burkitt Lymphoma Cells

Abstract: Burkitt lymphoma (BL) is a rapidly growing tumor, characterized by high anabolic requirements. The MYC oncogene plays a central role in the pathogenesis of this malignancy, controlling genes involved in apoptosis, proliferation, and cellular metabolism. Serine biosynthesis pathway (SBP) couples glycolysis to folate and methionine cycles, supporting biosynthesis of certain amino acids, nucleotides, glutathione, and a methyl group donor, S-adenosylmethionine (SAM). We report that BLs overexpress SBP enzymes, pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 48 publications
2
34
0
Order By: Relevance
“…In addition, EZH2 was shown to promote MYC expression by inhibiting the MYC-targeting miR-494-3p, resulting in a positive feedback loop between MYC, miR-26a/b-5p, EZH2, and miR-494-3p, which ensured high MYC levels and proliferation of BL [17,42]. A recently published study also confirmed the interplay between MYC, miR-494-3p, and EZH2 in BL [43].…”
Section: Discussionmentioning
confidence: 76%
“…In addition, EZH2 was shown to promote MYC expression by inhibiting the MYC-targeting miR-494-3p, resulting in a positive feedback loop between MYC, miR-26a/b-5p, EZH2, and miR-494-3p, which ensured high MYC levels and proliferation of BL [17,42]. A recently published study also confirmed the interplay between MYC, miR-494-3p, and EZH2 in BL [43].…”
Section: Discussionmentioning
confidence: 76%
“…Additional chromosomal abnormalities, recurrent abnormally expressed transcripts and/or gene mutations are also detected in BL/BAL patients and have roles in the initiation, progression and aggressiveness of the disease [5]. For instance, somatic mutations of TCF3 can activate the PI3K/MAPK/MTOR pathway, in part by increasing a tonic form of B cell receptor signaling, and patients with germline mutations in the SH2 domain protein 1A gene (SH2D1A) suffer from an increased risk of BL/BAL [6].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the increased fatty acid catabolism was associated with a decrease of trimethylation of histone H3 lysine 27 (H3K27me3) [15,16] which was also an independent prognostic factor for breast cancer [17,18] . Furthermore, many studies have found that the decreased level of H3K27me3 suppressed the transcription of oncogene MYC which was essential for the expression of GLS [19,20] . Thus, the relationship between GLS and H3K27me3 was intriguing, which may affect the prognostic role of GLS on breast cancer.…”
Section: Introductionmentioning
confidence: 99%